2016
DOI: 10.14814/phy2.12854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oscillatory changes in hippocampus and amygdala after deep brain stimulation of the infralimbic prefrontal cortex

Abstract: Deep brain stimulation (DBS) is a new investigational therapy that has generated positive results in refractory depression. Although the neurochemical and behavioral effects of DBS have been examined, less attention has been paid to the influence of DBS on the network dynamics between different brain areas, which could contribute to its therapeutic effects. Herein, we set out to identify the effects of 1 h DBS in the infralimbic cortex (IL) on the oscillatory network dynamics between hippocampus and basolatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Hz; Cervera-Ferri et al, 2016). In agreement with these results, clinical studies have shown that diminished SW activity in depression is restored after effective antidepressant treatments (Thase, 1997;Duncan et al, 2013).…”
Section: Cea Stimulation Induces a Stable Slow Wave In The Ilmentioning
confidence: 54%
See 3 more Smart Citations
“…Hz; Cervera-Ferri et al, 2016). In agreement with these results, clinical studies have shown that diminished SW activity in depression is restored after effective antidepressant treatments (Thase, 1997;Duncan et al, 2013).…”
Section: Cea Stimulation Induces a Stable Slow Wave In The Ilmentioning
confidence: 54%
“…Diminished slow oscillatory activity has been reported in two different animal models of depression (Voget et al ; Zheng & Zhang ), and reduced sleep SW activity (ranging from 1 to 4 Hz), has been postulated to be a biomarker of Major Depression Disease (Duncan & Zarate, ). Recently, this assertion has been extended to lower frequencies (<1.5 Hz; Cervera‐Ferri et al, ). In agreement with these results, clinical studies have shown that diminished SW activity in depression is restored after effective antidepressant treatments (Thase, ; Duncan et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In rodents, theta oscillations in the hippocampus were restored by stimulating the fornix, and spatial working memory task performance was improved (Bick and Eskandar, 2016). Also, after application of DBS in the infralimbic cortex fin rodents, the cognitive function and memory were improved, and theta oscillations in the hippocampus were restored (Cervera Ferri et al, 2016). An improvement in working memory was found after electrical stimulation of the central thalamus (CT) in object recognition memory tasks in rodents (Mair and Hembrook, 2008).…”
Section: Introductionmentioning
confidence: 99%